Peran Kalangan Milenial Terhadap Pengembangan Ekonomi Syariah Di Kabupaten Mandailing Natal - Rahmat, Paisal; Fitri, Meliani; Hanum Lubis, Fadhilah; Fauzi, Muhammad (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2023)
Millennials are people who are very attached to technology and the internet. Millennials prefer everything that is instant and efficient. The role of millennials in the sharia economy in Indonesia is to develop technology that can facilitate the Indonesian people in carrying out economic activities that are more efficient and not wasting time, millennials can disseminate sharia economic products through social media in Indonesia or abroad. This article aims to determine the role of millennials in the Islamic economy in Indonesia. The instrument in this study is an inductive thinking model and interviews with research informants. Based on interviews conducted by researchers, they found that millennials have had a positive impact on the Islamic economy in Indonesia, namely: 1) introducing Islamic economics to society, 2) developing Islamic economic products, 3) adding new innovations to the Islamic economy through existing technology.